The Relationship Between Gratitude and Happiness in Year 12 High School Students: Hubungan Antara Kebersyukuran dan Kebahagiaan pada Siswa Kelas 12 Sekolah Menengah Atas - Sriaissah, Agnes; Maryam, Effy Wardati (Psikologia : Jurnal Psikologi, 2022)
A student is every person who is officially registered to take lessons in the world of education, students should in carrying out their duties want happiness. Happiness is the life goal of each individual in this case is a student to determine his future. But in reality many students often get unhappiness problems, such as anxiety, fear, negative emotions, relationships with other people. Student happiness in school can be obtained from various factors. Factors that affect a person's level of happiness include gratitude, marital status, age, health, occupation, religion, gender, education level, welfare, and others. Grateful students tend to have positive emotions, pride, hope, enthusiasm, forgiveness, and feelings of joy. Based on this phenomenon, the researcher considers it necessary to conduct research with the aim of knowing the relationship between Gratitude and Happiness for Class XII Students of Hang Tuah 5 High School Sidoarjo. This study uses correlational quantitative methods, with a total sample of 207 students who were taken using the simple saturated technique. The data collection technique in this study uses two psychology models with a Likert scale, namely gratitude and happiness. Data analysis was carried out using the help of SPSS 20 Version for Windows. The results of the analysis of this study found that the correlation coefficient was 0.831 with a significance of 0.000 <0.05, which means that there is a positive relationship between gratitude and happiness. So the higher the gratitude, the higher the happiness. The results of the determination test in this study showed 0.685 (adjusted R Square) proving that in this study the gratitude variable gave an effective contribution of 68.5% to student happiness.